Vision- and Health-Related Quality of Life in Patients With Behcet Uveitis - AKMAN, MEHMET (AMER MEDICAL ASSOC, 2010)
Objective: To investigate vision- and health-related quality of life in patients with Behcet disease. Methods: Fifty-one consecutive patients with Behcet uveitis were enrolled in the study from January 1 through June 30, 2008. The National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25) and the 36-Item Short Form Health Survey (SF-36) were administered. Sociodemographic and clinical data were also collected. Main outcome measures were comparison of the NEI-VFQ-25 and SF-36 subscale item scores among subgroups and multivariate analysis of the NEI-VFQ-25 and SF-36 subscale item scores. Results: Patients rated the general health subscale score of the NEI-VFQ-25 and all subscale item scores of the SF-36 lower than the NEI-VFQ-25 subscales related to vision. The NEI-VFQ-25 subscale item scores showed significant differences with respect to age, educational level, Behcet uveitis activity and severity, and visual acuity in the better and worse eyes. The SF-36 subscale item scores revealed significant differences according to sex, educational level, and the systemic treatment used. In the best model of linear regression, independent variables accounted for 57.0% of the variance in the NEI-VFQ-25 subscale item (color vision subscale; adjusted R(2)=0.57, P<.001) and for only 23.0% of the variance in the SF-36 subscale item score (role limitation owing to emotional problems subscale; adjusted R(2)=0.23, P=.004). Conclusions: General health is more affected than visual functioning in patients with Behcet uveitis. Sociodemographic and clinical variables had a significant effect on vision- and health-related quality of life. Multivariate analysis of the NEI-VFQ-25 and SF-36 subscales revealed that each subscale item score is affected by additional factor(s) other than those analyzed here.
Keywords: INTERFERON ALPHA-2A; TURKISH VERSION; DISEASE; QUESTIONNAIRE; RELIABILITY; VALIDITY; THERAPY; CANCER; SF-36